2017
DOI: 10.1080/14764172.2017.1341048
|View full text |Cite
|
Sign up to set email alerts
|

The effects of low-level laser therapy on the healing of bone defects in streptozotocin-induced diabetic rats: A histological and morphometric evaluation

Abstract: LLLT application promoted vascularization and new bone formation in animals with DM to a limited extent, since it was unable to support the healing process up to the level of non-diabetic animals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 36 publications
0
15
0
1
Order By: Relevance
“…PBMT involves radiation from the red to infrared regions, with the latter being most cited in the literature as effective in the early stages of bone repair during the reconstruction process. This is because, at the early stages, there is a large amount of differentiating cells, and reduction of these cells at a late time of repair reduces the PBMT-related osteostimulatory potential [25,48,64].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PBMT involves radiation from the red to infrared regions, with the latter being most cited in the literature as effective in the early stages of bone repair during the reconstruction process. This is because, at the early stages, there is a large amount of differentiating cells, and reduction of these cells at a late time of repair reduces the PBMT-related osteostimulatory potential [25,48,64].…”
Section: Discussionmentioning
confidence: 99%
“…Most experimental and clinical studies describe that PBMT aids in the process of tissue regeneration, demonstrating biological modulatory effects on cell differentiation [9,16,17]. Photobiomodulation of bone tissue seems to increase the results of fracture repair [18], periodontal tissue [19], implant osseointegration [20] and bone reconstruction with or without biomaterials [15,[21][22][23][24][25]. Its application in clinical practice with the purpose of assisting healing after bone graft reconstruction surgery [26] is still poorly described in the scientific literature.…”
Section: Introductionmentioning
confidence: 99%
“…For example, studies found that LLI could promote the regeneration of gastrocnemius muscle after cold injury and enhance neovascularization after injury, indicating a potential role of PBM on regeneration and angiogenesis after muscle injury [209,210]. In addition, the beneficial effects of PBM have been experimentally demonstrated on recurrent aphthous stomatitis, skin burn injuries, diabetes mellitus, sports injuries, and osteoarthritis [211][212][213][214][215][216]. Most significantly, PBM is able to confer its photobiological effect at the cellular level without thermal and toxic effects [217].…”
Section: Methylene Blue and Photobiomodulation As Therapeutic Approachesmentioning
confidence: 99%
“…[6][7][8] One of the debated treatment modalities, despite its common use, is low-level laser therapy (LLLT) [9][10][11][12][13][14] that is used in the treatment of many diseases. [15][16][17][18][19][20] Imani et al and Munguia et al concluded that almost 60% of the literature between 2000 to 2018 demonstrated that LLLT was useful in reducing pain and trigger point sensitivity, improving the quality of life. 21,22 Momenzadeh et al 23 reached the same result.…”
Section: Introductionmentioning
confidence: 99%